Advances in Geo-Science and Geo-Structures Select Proceedings of GSGS 2020 - Choudhary, Awdhesh Kumar; Mondal, Somenath; Metya, Subhadeep; Babu, G. L. Sivakumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents select proceedings of the National conference on Geo-Science and Geo-Structures (GSGS 2020). It provides sustainable solutions to various challenges encountered in the field of geotechnical engineering. The topics presented include advanced characterization to study the behavior of geomaterials, shallow and deep foundations including tunneling, use of geosynthetics and other soil reinforcing materials in minimizing slope failures and landslides, dynamics of soils and foundations, and its connection with energy geotechnics, transportation geotechnics, and offshore geotechnics. The book further highlights various aspects of ground improvement techniques by incorporating the use of industrial by-products, forensic analyses of geo-structures, instrumentation and sensing techniques in geotechnical engineering and issues associated with geo-environmental engineering. The book will be a valuable reference for budding researchers, academicians, practitioners and policymakers interested in sustainable practices associated with geotechnical engineering and related domains.
Estimation of Landfill Settlement using Different Models -- Prediction of Liquefaction using Reliability Based Regression Analysis -- Modeling of Consolidation Considering Coupled Soil-Fluid Interaction -- Comparative Assessment of Kurukshetra City Waste Dumping Sites using RIAM Analysis: A Case Study -- Effect of Soil Structure Interaction on Seismic Response of Buildings -- Improvement in the Properties of Red Soil using Granulated Blast Furnace Slag -- Numerical Modeling of Soil Nailed Slope using Drucker-Prager Model -- Winkler$1 (Bs Based Parametric Analysis of Unplugged Short Pipe Pile -- Improvement of Strength Behaviour of Fly Ash and Cement Stabilized Soil with Glass Fiber Reinforcement -- Stability Prediction of a Two-Layered Soil Slope -- A Study on Geotechnical Characteristics of Black Cotton Soil Treated with Red Mud and GGBS -- Finite Element Analysis of Buried Pipe in Soil Slope -- Studies on the Piled Raft Foundation for a High Rise Building using Finite Element Modeling -- Seismic Response of Soil Like Material in MSW Landfill using Equivalent Linear Approach -- Numerical Analysis on Load Carrying Mechanism of Single Pile Due to Twin Stacked Tunnelling -- Negative Skin Friction on Piles: State of the Art.s
Keywords: Engineering geology; Geotechnical engineering; Foundations; Underground construction; Rock mechanics; Soil mechanics; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Foundation Engineering; Underground Engineering and Tunnel Construction; Soil and Rock Mechanics; Geotechnical engineering -- Congresses